The Taxation of Petroleum and Minerals. - Daniel, Philip (Routledge Explorations in Environmental Economics, 24., 2010)
Oil, gas, and mineral deposits are a substantial part of the wealth of many countries, not least in developing and emerging market economies. Harnessing some part of that wealth for fiscal purposes is critical for economic development. This book shows how the harnessing in few areas of economic life are the returns to good policy.